Identification of Flavonoid Compounds from Purified Extract of Beetroot Leaf (Beta Vulgaris L) - Diah Pratimasari; Dian Puspitasari (Indonesian Journal of Global Health Research, 2022)
Flavonoids are one of the secondary metabolites that have good pharmacological activity. One of the plants that contain flavonoid compounds is beetroot leaves. Beetroot leaves are waste or crop residues from beetroots that are rarely used. The use of extracts from plant leaves in the pharmaceutical world needs to consider the presence of ballast substances that can affect the activity of the extract. However, the purification process using organic solvents has the potential to lose the content of compounds contained in the extract, one of which is flavonoids. Therefore, this study aims to examine the profile of flavonoid compounds contained in purified extracts of beetroot leaves compared to the extract content. The study began with the manufacture of beetroot leaf extract, followed by the purification process of the extract using n-hexane and ethyl acetate as solvents. Extracts and purified extracts of beetroot leaves were then analyzed using Thin Layer Chromatography (TLC), UV-Vis Spectrophotometer and Infra Red (IR) Spectrophotometer. The results showed that the profile of flavonoid compounds contained in purified extract of beetroot leaves had similarities with the profile of flavonoid compounds found in beetroot leaf extract.